Characteristics of Meiyu Seen From Multiple Observational Analyses and Reanalyses - Mingjun Tong (Earth and Space Science, 2021)
Abstract This study examines characteristics of Meiyu during the Meiyu season from June 1 to July 31 for 1998–2017 using two observational analyses (i.e., Tropical Rainfall Measuring Mission [TRMM] and Global Precipitation Climatology Project [GPCP]) and four reanalysis data sets (i.e., Modern‐Era Retrospective Analysis for Research and Applications, Version 2 [MERRA2], ERA5, JRA55, and NCEP/DOE). The Meiyu mean precipitation from GPCP is slightly larger than TRMM but GPCP has smaller precipitation variance as compared with TRMM. MERRA2 and ERA5 are consistent with TRMM precipitation in terms of both mean and variance patterns, while JRA55 (NCEP/DOE) has smaller mean precipitation and variance in the middle and lower reaches of the Yangtze River in China (near southern Japan). For the interannual variability of the precipitation averaged over the Meiyu region, the correlation with TRMM from high to low is ranked by MERRA2, GPCP, JRA55, ERA5, and NCEP/DOE. For the Meiyu evolution, GPCP, MERRA2, ERA5, and JRA55 capture the gradual northward movement of the Meiyu belt from June 2 to July 10, as shown in TRMM, but NCEP/DOE does not. For the large‐scale meteorology conditions for the strong and weak Meiyu years, the relative humidity vertical profiles from the four reanalyses are analyzed. All reanalyses except NCEP/DOE show that the relative humidity is larger in the strong Meiyu years than that in the weak Meiyu years and relative humidity over Japan and South Korea is larger than that over the lower reaches of the Yangtze River. It is recommended that TRMM and MERRA2 reanalysis be used for the investigations of the Meiyu precipitation and variability and large‐scale conditions.